Design and Modeling of an Integrated Micro-Transformer in a Flyback Converter - M. Derkaoui M. Derkaoui; A. Hamid A. Hamid; T. Lebey T. Lebey; R. Melati R. Melati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
This paper presents the design and modeling of a square micro-transformer for its integration in a flyback converter. From the specifications of the switching power supply, we determined the geometric parameters of this micro-transformer. The π-electrical model of this micro-transformer highlights all parasitic effects generated by stacking of different material layers and permits to calculate the technological parameters by using the S-parameters. A good dimensioning of the geometrical parameters reduces efficiently the energy losses in the micro-transformer and permits to reach the desirable value of the converter output voltage. We have also simulated the electromagnetic effects with the help of the software FEMLAB3.1 in two cases. The first case, without ferromagnetic core, the second case with ferromagnetic core, in order to choose the micro-transformer that has better electromagnetic compatibility with the vicinity components. To validate dimensioning of the geometrical and technological parameters, we have simulated with the help of the software PSIM6.0, the equivalent electrical circuit of the converter containing the electrical circuit of the dimensioned planar micro-transformer.